2014
DOI: 10.1371/journal.pone.0093123
|View full text |Cite
|
Sign up to set email alerts
|

Covalent and Density-Controlled Surface Immobilization of E-Cadherin for Adhesion Force Spectroscopy

Abstract: E-cadherin is a key cell-cell adhesion molecule but the impact of receptor density and the precise contribution of individual cadherin ectodomains in promoting cell adhesion are only incompletely understood. Investigating these mechanisms would benefit from artificial adhesion substrates carrying different cadherin ectodomains at defined surface density. We therefore developed a quantitative E-cadherin surface immobilization protocol based on the SNAP-tag technique. Extracellular (EC) fragments of E-cadherin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 54 publications
(75 reference statements)
9
53
0
Order By: Relevance
“…2), albeit at levels much reduced when compared to RGD-conjugated gels (HAVDI attachment ~10% of RGD attachment). This is consistent with previous reports showing that the first two extracellular domains of N-Cadherin (in which the HAVDI sequence resides) allow for weak adhesive interactions when compared to the full ectodomain 41 . Next, we examined 1 mM: 1 mM peptide combinations of HAVDI and RGD across a physiologic range of substrate stiffness, and noted no significant difference in spread area between HAVDI/RGD and scram/RGD groups (Fig.…”
Section: Tunable Hydrogels Presenting Cell-cell and Cell-ecm Ligandssupporting
confidence: 93%
“…2), albeit at levels much reduced when compared to RGD-conjugated gels (HAVDI attachment ~10% of RGD attachment). This is consistent with previous reports showing that the first two extracellular domains of N-Cadherin (in which the HAVDI sequence resides) allow for weak adhesive interactions when compared to the full ectodomain 41 . Next, we examined 1 mM: 1 mM peptide combinations of HAVDI and RGD across a physiologic range of substrate stiffness, and noted no significant difference in spread area between HAVDI/RGD and scram/RGD groups (Fig.…”
Section: Tunable Hydrogels Presenting Cell-cell and Cell-ecm Ligandssupporting
confidence: 93%
“…While classic trans cadherin bonds are mediated by homophilic strand swapping of an N-terminal tryptophan residue into a hydrophobic pocket of its binding partner 13 , we previously demonstrated that the trans tip-link bond has a far more extensive, amphiphilic "handshake" interface involving ~30 amino acids in the first two extracellular (EC) domains of each protein 8 . Although the dissociation constant of a single tip-link bond is approximately the same as for classic cadherins 8,[14][15][16][17][18] , little is known about how the tip-link bond responds to force.…”
Section: Main Textmentioning
confidence: 99%
“…1f). Compared with classic cadherins (mean lifetime ≈ 0.75 s, fβ ≈ 5.5 pN) [14][15][16][17][18] , the single tip-link bond is significantly more resistant to mechanical force (Fig. 1g).…”
Section: Main Textmentioning
confidence: 99%
“…Traditionally, cell-cell adhesion is described as being achieved by the symmetric interactions of the first extracellular domains (EC1) of cadherins on neighbouring cells (trans-interaction) [63,66]; cadherins on the same cell also interact with each other (cis-interaction) through the EC1 domain of one and the EC2 domain of the other [63,66,67]. More recently, it has been described that optimal cell-cell adhesion (50-70 pN) is achieved by all five EC domains of E-cadherin, and with a cellcell separation of 5-11 nm [64] ( figure 1). E-, P-and N-cadherin were the first cadherins identified, and can all mediate cell-cell adhesion in this fashion [62,68]: -E-cadherin (cadherin-1, 120 kDa): the main mediator of cell -cell adhesion in epithelial tissues and expressed by most normal epithelial cells [19,60,61,[68][69][70].…”
Section: Cadherinsmentioning
confidence: 99%
“…Traditionally, cadherins on neighbouring cells adhere via EC1 domains, although more recent research suggests that all five EC domains are required for optimal adhesion [64]. Figure 2.…”
Section: Cadherin Switchingmentioning
confidence: 99%